AI-Based Surveillance Framework for Physical Violence Detection - Anala M. R., Srividya M. S. (International Journal of Intelligent Systems and Applications in Engineering, 2024)
This research paper presents a groundbreaking approach to addressing the societal problem of physical abuse, which affects various demographic groups, including children, women, and older people, especially in domestic and workplace environments. The complexity of these situations, especially when the abuser and victim know each other, highlights the need for an advanced solution. The paper introduces a novel hybrid deep-learning framework to detect and prevent physical abuse and address this. The framework utilizes human action recognition, leveraging a 3D convolutional neural network (CNN) to meticulously analyze human actions in such contexts. The deep learning model is further enhanced by employing transfer learning techniques with ResNet-18 and GoogleNet models. These models are trained using the UBI fight and UCF crime datasets, which are public resources for video analysis, to identify instances of physical abuse. A significant innovation in this model is the transformation of 2D kernels into 3D kernels, which allows for an improved extraction of features in both temporal and spatial dimensions from the video data. Additionally, a bilinear Long Short-Term Memory (LSTM) layer is integrated into the model to capture more extended material information, thus improving the analysis of human actions. The results of this hybrid model in detecting physical abuse are promising, showing marked improvements in performance metrics due to the shift from 2D to 3D kernels and the inclusion of bilinear LSTM